2016
DOI: 10.1186/s12877-016-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

Delirium is not associated with anticholinergic burden or polypharmacy in older patients on admission to an acute hospital: an observational case control study

Abstract: BackgroundOlder people are commonly prescribed multiple medications, including medications with anticholinergic effects. Polypharmacy and anticholinergic medications may be risk factors for the development of delirium.MethodsPatients from a medical admission unit who were over 70, with DSM-IV diagnosed delirium and patients without delirium, were investigated. Number of drugs prescribed on admission and anticholinergic burden using two scales (the Anticholinergic Cognitive Burden Scale [ACB] and the Anticholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 35 publications
7
27
0
Order By: Relevance
“…On the other hand, although polypharmacy in older hospitalized patients is associated with delirium in many studies [10, 28, 29], our study did not confirm this association. This could be consistent with data by Moorey et al [30], showing that the number of prescribed drugs inversely correlated with age. Along the same line, our dementia patients (who were also older) had less polypharmacy than those without dementia.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, although polypharmacy in older hospitalized patients is associated with delirium in many studies [10, 28, 29], our study did not confirm this association. This could be consistent with data by Moorey et al [30], showing that the number of prescribed drugs inversely correlated with age. Along the same line, our dementia patients (who were also older) had less polypharmacy than those without dementia.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that anticholinergic drug exposure measured with the ARS is associated with delirium, is in agreement with the results of previous studies performed in critically ill patients (Wolters et al 2015), palliative care patients (Zimmerman et al 2014), patients with Parkinson's disease (Crispo et al 2016) and older nursing home residents (Landi et al 2014). Also, previous studies found no association between anticholinergic drug exposure, measured with the ACB or the Anticholinergic Drug Scale, and delirium in older hospitalized patients (Moorey et al 2016;Campbell et al 2011;Wolters et al 2015). These findings strengthen the observation that results may differ depending on which scale is used when assessing anticholinergic drug exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Also, previous studies found no association between anticholinergic drug exposure, measured with the ACB or the Anticholinergic Drug Scale, and delirium in older hospitalized patients (Moorey et al. ; Campbell et al. ; Wolters et al.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, other investigations have not identified an association between AC burden and specific clinical adverse effects (e.g. delirium) . Although differences exist between findings, the Beers criteria, from the American Geriatrics Society, state that the use of medications that are classified as strong ACs should be avoided in the elderly due to an increased risk of confusion, dry mouth, constipation and other AC effects or toxicity .…”
Section: Introductionmentioning
confidence: 98%
“…delirium). 6,7 Although differences exist between findings, the Beers criteria, from the American Geriatrics Society, state that the use of medications that are classified as strong ACs should be avoided in the elderly due to an increased risk of confusion, dry mouth, constipation and other AC effects or toxicity. 8 If alternative treatments with similar efficacy, but no associated AC side effects, are available for use in a particular therapeutic area, it might be possible to reduce the AC burden experienced by the patient.…”
Section: Introductionmentioning
confidence: 99%